2016
DOI: 10.1016/j.injury.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Anteroinferior 2.7-mm versus 3.5-mm plating of the clavicle: A biomechanical study

Abstract: While our results show clear mechanical superiority of 3.5-mm reconstruction plates over 2.7-mm plates, superior results in the clinical setting may not necessarily translate. With exceptional mechanical strength also noted for the 2.7mm plate, well above the biomechanical properties of an intact clavicle, these results may obviate the need for robust plates in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Despite the poorer biomechanical stability, 2.7 mm anteroinferior plating showed absolute values which easily withstood physiological forces. The cyclical test protocol used in the study led in neither of the 2 groups to implant failure [17].…”
Section: Claviclementioning
confidence: 99%
“…Despite the poorer biomechanical stability, 2.7 mm anteroinferior plating showed absolute values which easily withstood physiological forces. The cyclical test protocol used in the study led in neither of the 2 groups to implant failure [17].…”
Section: Claviclementioning
confidence: 99%
“…[5] As a result, open reduction internal fixation of midshaft clavicle fractures, through use of a plate or intramedullary device, has become a common treatment approach. [2,6]…”
Section: Introductionmentioning
confidence: 99%
“…Previously, several biomechanical studies for distal clavicle fracture evaluated and compared the fixation strength between nonanatomical and anatomical plates and between locking head and nonlocking head screws. [26][27][28][29][30] previous studies reported that about 400-600 N strength is required for failure of fixation due to pull-out. 26,28,31 Considering the ultimate pullout strength of 235 N in this study, the distal clavicle locking plate can only be used in cases that allows three or more screws in lateral fixation, due to the significant possibility of failure with lateral fixation using only two screws.…”
Section: Discussionmentioning
confidence: 99%